PEREMPUAN DAN PONSEL PINTAR: REALITAS IBU RUMAH TANGGA MASA KINI - Dewi Kartika, Dewa Ayu; Kebayantini, Ni Luh Nyoman; Sastri Mahadewi, Ni Made Anggita (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
Smartphones have been used by various groups, including housewives. This is because smartphones provide benefits in communication, entertainment and self-actualization. This study uses a qualitative approach with a descriptive type of research. The theory chosen in this study is the Cyberfeminism Theory popularized by Sandie Plant. This theory talks about the equality of use of technology for women, who have identified technology with men. Based on the results of this study, the use of smartphones by housewives is considered by people around to be very good and the use of smartphones for housewives is considered quite helpful although there are also negative views about excessive use of cell phones by housewives. There are various positive and negative impacts caused by smartphones. This study also explains that the technology of housewives can still be smart, not isolated from the outside world and equal in access to technology and can actualize themselves. Keywords: smartphone, housewife, point of view, impact